Fishers, Monks and Cadres Navigating State, Religion and the South China Sea in Central Vietnam - Roszko, Edyta (University of Hawai'i Press, 2020)
This remarkable and timely ethnography explores how fishing communities living on the fringe of the South China Sea in central Vietnam interact with state and religious authorities as well as their farmer neighbors - even while handling new geopolitical challenges. The focus is mainly on marginal people and their navigation between competing forces over the decades of massive change since their incorporation into the Socialist Republic of Vietnam in 1975. The sea, however, plays a major role in this study as does the location: a once-peripheral area now at the center of a global struggle for sovereignty, influence and control in the South China Sea. The coastal fishing communities at the heart of this study are peripheral not so much because of geographical remoteness as their presumed social 'backwardness'; they only partially fit into the social imaginary of Vietnam's territory and nation. The state thus tries to incorporate them through various cultural agendas while religious reformers seek to purify their religious practices. Yet, recently, these communities have also come to be seen as guardians of an ancient fishing culture, important in Vietnam's resistance to Chinese claims over the South China Sea. The fishers have responded to their situation with a blend of conformity, co-option and subtle indiscipline. A complex, triadic relationship is at play here. Within it are various shifting binaries - e.g. secular/religious, fishers/farmers, local ritual/Buddhist doctrine, etc. - and different protagonists (state officials, religious figures, fishermen and -women) who construct, enact, and deconstruct these relations in shifting alliances and changing contexts. Fishers, Monks and Cadres is a significant new work. Its vivid portrait of local beliefs and practices makes a powerful argument for looking beyond monolithic religious traditions. Its triadic analysis and subtle use of binaries offer startlingly fresh ways to view Vietnamese society and local political power. The book demonstrates Vietnam is more than urban and agrarian society in the Red River Basin and Mekong Delta. Finally, the author builds on intensive, long-term research to portray a region at the forefront of geopolitical struggle, offering insights that will be fascinating and revealing to a much broader readership. From the backflap: "As geopolitical tensions rise in and around Vietnam's Eastern Sea (known elsewhere as the South China Sea), too little is known about the richly variegated and complex social life along Vietnam's coastline. This detailed and painstakingly researched ethnography from coastal central Vietnam places the disputes over oceanic sovereignty within a longer history of social life in this fascinating but curiously understudied part of Vietnam. Revealing how entangled Vietnamese economic and spiritual life is with the sea, we learn how ritual, religion, economy and politics all course through the heart of changing relations among state and society. Everyday actors navigate the categories of state, society and religion like they sail the seas with the stars; the categories are both fixed and in motion, guiding life at the interface of sea and shore, even as everyday actors constantly shift their position among them." -Erik Harms, Yale University "Roszko's excellent analysis of state-society dynamics in contemporary Vietnam reflects her many years of living in, and studying, these communities. Her discoveries about personal, political and religious life are perceptive and fascinating. This book will be a significant contribution to studies of local political power in Vietnam and throws new light on the ways the state and communities have engaged with aspects of the disputes in the South China Sea." -Bill Hayton, author of The South China Sea: The Struggle for Power in Modern Asia.